Global Scenario on Wetlands and Plant Adaptation Mechanisms in Water logging Condition: A Critical Review - Nayak, Amit Prakash; Sahu, Vibha (International Journal of Economic Plants, 2021)
Wetlands are shallow to intermittently flooded ecosystems that are commonly known as swamps, bogs, marshes and sedge meadows. Wetlands are sometimes described as “the kidney of the landscape” because they function as the downstream receivers of water and waste from both natural and human sources. Water logging is one of the major problems in wetlands that restrict oxygen movement from the atmosphere to the soil resulting in anaerobic conditions. For such type of conditions, plants and microbial species require special adaptations. This review summarizes a comprehensive overview of distribution, major types of wetlands in global level and in India (including Ramsar Sites of India). It also signifies different plant adaptation mechanisms in these adverse conditions.